Traditional Human Populations and Nonhuman Primates Show Parallel Gut Microbiome Adaptations to Analogous Ecological Conditions - Ashok K. Sharma (American Society for Microbiology, 2020)
ABSTRACT Compared with urban-industrial populations, small-scale human communities worldwide share a significant number of gut microbiome traits with nonhuman primates. This overlap is thought to be driven by analogous dietary triggers; however, the ecological and functional bases of this similarity are not fully understood. To start addressing this issue, fecal metagenomes of BaAka hunter-gatherers and traditional Bantu agriculturalists from the Central African Republic were profiled and compared with those of a sympatric western lowland gorilla group (Gorilla gorilla gorilla) across two seasons of variable dietary intake. Results show that gorilla gut microbiomes shared similar functional traits with each human group, depending on seasonal dietary behavior. Specifically, parallel microbiome traits were observed between hunter-gatherers and gorillas when the latter consumed more structural polysaccharides during dry seasons, while small-scale agriculturalist and gorilla microbiomes showed significant functional overlap when gorillas consumed more seasonal ripe fruit during wet seasons. Notably, dominance of microbial transporters, transduction systems, and gut xenobiotic metabolism was observed in association with traditional agriculture and energy-dense diets in gorillas at the expense of a functional microbiome repertoire capable of metabolizing more complex polysaccharides. Differential abundance of bacterial taxa that typically distinguish traditional from industrialized human populations (e.g., Prevotella spp.) was also recapitulated in the human and gorilla groups studied, possibly reflecting the degree of polysaccharide complexity included in each group’s dietary niche. These results show conserved functional gut microbiome adaptations to analogous diets in small-scale human populations and nonhuman primates, highlighting the role of plant dietary polysaccharides and diverse environmental exposures in this convergence. IMPORTANCE The results of this study highlight parallel gut microbiome traits in human and nonhuman primates, depending on subsistence strategy. Although these similarities have been reported before, the functional and ecological bases of this convergence are not fully understood. Here, we show that this parallelism is, in part, likely modulated by the complexity of plant carbohydrates consumed and by exposures to diverse xenobiotics of natural and artificial origin. Furthermore, we discuss how divergence from these parallel microbiome traits is typically associated with adverse health outcomes in human populations living under culturally westernized subsistence patterns. This is important information as we trace the specific dietary and environmental triggers associated with the loss and gain of microbial functions as humans adapt to various dietary niches.